Hak asasi manusia: Antara harapan dan realita di Indonesia - Karyanto, Rayhana Annisa (Maliki Interdisciplinary Journal, 2026)
Human Rights (HAM) are essentially rights inherent in every human being since birth, as a gift from God Almighty. The existence of these rights cannot be separated from human life, and the state has a non-negotiable obligation to respect and provide real protection for these rights. This journal seeks to examine in depth the veil that often occurs between the normative order contained in various regulations (expectations) and the actual conditions of the implementation of human rights enforcement in the field (reality) in Indonesia. This journal examines various incidents of human rights violations that occurred from the Old Order to the Reformation era, including a number of recent cases that are still hotly discussed. The findings of this journal indicate that although Indonesia actually has a collection of quite comprehensive and adequate legal frameworks, the effectiveness of its enforcement still faces various serious obstacles, which stem from the weak independence of judicial institutions, strong intervention of political interests, and the still low legal culture that lives in society. Therefore, this journal recommends the need to strengthen the capacity of relevant state institutions, implement comprehensive legal system reform, and increase human rights literacy massively and sustainably across all levels of society.